2016
DOI: 10.1111/jph.12472
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Trichoderma harzianum Isolates against Ceratocystis radicicola: pioneering a Biocontrol Strategy against Black Scorch Disease in Date Palm Trees

Abstract: Date palm is an important subsistence crop in arid regions due to its ability to grow under adverse environmental conditions such as high temperature, salinity and drought. Nevertheless, ideal conditions for its growth and production are also favourable to fungal diseases such as black scorch disease caused by Ceratocystis radicicola. The aim of this study was to develop a method of biological control through the isolation, identification and examination of the effectiveness of bioagents in controlling black s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This suggests that the Streptomyces strain isolated in this study can serve as a potential antifungal product against T. punctulata . Whilst a number of recent reports have focused on biological controls using species of Trichoderma or Chaetomium against T. punctulata or T. paradoxa growth ( Soytong et al, 2005 ; Chakrabarty et al, 2013 ; Al-Naemi et al, 2016 ), the current study demonstrates, for the first time, the feasibility of using a streptomycete actinomycete isolate as a BCA against black scorch disease caused by T. punctulata .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This suggests that the Streptomyces strain isolated in this study can serve as a potential antifungal product against T. punctulata . Whilst a number of recent reports have focused on biological controls using species of Trichoderma or Chaetomium against T. punctulata or T. paradoxa growth ( Soytong et al, 2005 ; Chakrabarty et al, 2013 ; Al-Naemi et al, 2016 ), the current study demonstrates, for the first time, the feasibility of using a streptomycete actinomycete isolate as a BCA against black scorch disease caused by T. punctulata .…”
Section: Discussionmentioning
confidence: 72%
“…Biological control, also known as biocontrol, can limit the increases in pathogen populations, and often suppress the plant tissue destroying activities of pathogens by other organism(s) (AbuQamar et al, 2017). In vitro and in vivo experiments using species of Trichoderma , Chaetomium or their antagonistic products were applied to control black scorch pathogens (Soytong et al, 2005; Sánchez et al, 2007; Ammar, 2011; Al-Naemi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…are very beneficial fungi and have the ability to control many pathogens (Fontenelle et al, 2011;Tchameni et al, 2011). Application of culture filtrates and spore suspension of T. harzianum reduced the size of necrotic spots of black scorch disease of date palm caused by Ceratocystis radicicola (Al-Naemi et al, 2016). T. harzianum is also known to reduce severity of leaf blotch of wheat caused by Zymoseptoria tritici (Stocco et al, 2016).…”
Section: Pot Trialmentioning
confidence: 99%
“…Trichoderma is among the most commonly used biocontrol agents and is an effective antagonist against plant pathogenic fungi ( Kumar and Mukerji, 1996;Stocco et al, 2016). Recent studies have shown that Trichoderma spp., especially T. harzianum, can control diseases caused by Rhizoctonia solani, Macrophomina phaseolina and Ceratocystis radicicola (Al-Naemi et al, 2016;Javaid et al, 2017b;Youssef et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation